Hannah Arendt and the fragility of human dignity - Macready, John Douglas (Lexington Books, 2018)
The quest for a political measure of human dignity -- Rethinking human dignity in dark times -- The worldliness of human dignity -- Conditional dignity and political personhood -- The right to a place in the world